DELOCALIZATION POLICY AND PRINCIPALS’ PERFORMANCE IN SECONDARY SCHOOLS: A CASE STUDY OF LOITOKTOK SUB-COUNTY IN KAJIADO COUNTY, KENYA - JOSEPH MUTIA MUSYOKA (Machakos University Press, 2025)
The concept of delocalization encompasses the transfer of teachers by their employers either voluntarily or involuntarily to another location which is not necessarily the county of the teacher's origin. The transfer of principals in some schools faced succession related disruptions. More so, the academic performance of the secondary schools has been on a downward trend where the examination malpractices were observed nationally. This study sought to establish the effects of delocalization policy on principals’ performance in Secondary Schools in Loitokitok Sub-County, Kajiado County. Specifically, the study sought to determine the effects of delocalization policy on principals’ management of students' discipline in secondary schools in Loitokitok Sub-County, to examine the effects of delocalization policy on principals’ curriculum supervision in secondary schools in Loitokitok Sub-County, to establish the effects of delocalization policy on principals’ infrastructure development in secondary schools in Loitokitok Sub-County and to determine the effects of delocalization policy on principals’ motivation of teachers in secondary schools in Loitokitok Sub-County. The study was guided by Collegial Leadership Theory and Agency Theory. The research design for the study was descriptive design with case study approach. There are 22 secondary schools in Loitokitok Sub-County therefore, the target population comprised of all the 22 principals and 286 teachers in Secondary Schools in Loitokitok Sub County in Kajiado County. The target population was stratified into three categories namely; Boys, Girls and Mixed Secondary Schools whereby 11 schools representing 50% were sampled with a total of 204 teachers. All the 11 Principals of the sampled schools were selected using purposive sampling while 30% of the 204 teachers of the sampled schools were sampled using simple random method. This resulted to an overall sample size of 72 respondents. Primary data was utilized which was collected using a questionnaire. This had both closed and open-ended questions covering the variables and the objectives of the study. Pilot study was undertaken prior to the actual study to help determine the instruments' accuracy, clarity, and applicability. The data collection procedure began by seeking the letter of approval from Machakos University followed by research permit from National Commission for Science, Technology and Innovation (NACOSTI). The study found that the principals offer good management skills in order to have students portray good behavior and that the respondents have attended in service courses on curriculum implementation. The study found that students pay fees timely which boost the smooth school operations and that the respondents create a conducive working environment in the school. The study concluded that teacher motivation is significantly influenced by both curriculum supervision and infrastructure. However, principal performance is not significantly correlated with any of the four variables, which may indicate that other unmeasured factors influence principal performance, or the measurement of performance may need refinement. It was recommended that since principals demonstrate good management skills that support good student behavior, education stakeholders should invest in continuous leadership training and mentorship programs for school leaders. School Boards and education offices should recognize and incentivize effective principals to maintain high standards of school leadership.